Systemic Therapy in Metastatic or Unresectable Well-Differentiated/Dedifferentiated Liposarcoma - McGovern, Yevette; Zhou, Charlie D.; Jones, Robin L. (Frontiers in Oncology, 2017)
Liposarcoma is one of the most common subtypes of soft tissue sarcoma and consists of three main subtypes, of which well-differentiated liposarcoma (WDLS) and de-differentiated liposarcoma (DDLS) account for 40-45%. The current mainstay of systemic treatment for patients with metastatic or unresectable disease remains doxorubicin with or without ifosfamide in the first line setting. Recently eribulin and trabectedin have been approved by the FDA for recurrent liposarcomas and progress in molecular characterisation of these tumours has opened up new and potential novel treatment targets. This review will focus on the evidence base for current treatment strategies and will also discuss potential future options.